2004
DOI: 10.1002/ijc.20378
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the p27Kip1‐mediated antiproliferative effect of trastuzumab (Herceptin) on HER2‐overexpressing tumor cells

Abstract: The oncogenic activity of the overexpressed HER2 tyrosine kinase receptor requires its localization in the plasma membrane. The antitumor effect of anti-HER2 antibodies (Abs) is mainly dependent on receptor downregulation and comprises p27 Kip1 -mediated G 1 cell cycle arrest. However, one major limitation of anti-HER2 therapy is the reversibility of tumor growth inhibition after discontinuation of treatment caused by the mitogenic signaling associated with cell surface receptor re-expression. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 59 publications
(65 reference statements)
2
24
1
Order By: Relevance
“…As previously described, p27 kip1 mediates G 0 /G 1 arrest and antiproliferative effects in BT-474 and SK-BR-3 cells induced by Herceptin (Marches and Uhr, 2004). Here, we raised the question whether the combinatorial treatment with Herceptin and Plk1-specific siRNA enhances the expression of p27 kip1 significantly compared with the application of single agents.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…As previously described, p27 kip1 mediates G 0 /G 1 arrest and antiproliferative effects in BT-474 and SK-BR-3 cells induced by Herceptin (Marches and Uhr, 2004). Here, we raised the question whether the combinatorial treatment with Herceptin and Plk1-specific siRNA enhances the expression of p27 kip1 significantly compared with the application of single agents.…”
Section: Resultsmentioning
confidence: 69%
“…Although the treatment of HER2-positive cells with Herceptin alone does not induce apoptosis (Xia et al, 2006), the combination with Plk1-specific siRNAs showed apoptosis based on cleavage of caspases 3 and 9. In addition, after pre-treatment of SK-BR-3 cells with Plk1-specific siRNAs, we observed an induction of p27 kip1 which mediates the G 0 /G 1 arrest and the antiproliferative effect of Herceptin (Lane et al, 2000;Marches and Uhr, 2004;Dubska et al, 2005). One experimental approach to overcome Herceptin resistance is the transfection of p27 kip1 which restores Herceptin sensitivity to resistant cell lines (Nahta et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…While some studies show that trastuzumab downregulates HER2 in HER2-overexpressing tumor cells (Cuello et al, 2001;Citri et al, 2002;Lee et al, 2002;Marches and Uhr, 2004), other studies clearly show that it does not (Austin et al, 2004;Longva et al, 2005). Part of the complexity in this field was resolved when it was determined that trastuzumab binds and internalizes with surface HER2 but re-emerges with HER2 at the surface, merely accompanying HER2 passively along its normal endocytic recycling route (Austin et al, 2004).…”
Section: Mechanism Of Action Of Trastuzumab -Her2 Downregulationmentioning
confidence: 99%
“…The antiproliferative effect of mAb 4D5 or trastuzumab in cell-culture models is associated with the induction of p27 and G1 block (Lane et al, 2000;Marches and Uhr, 2004;Le et al, 2005). Trastuzumab affects the expression of tumor angiogenic factors and exhibits certain anti-angiogenic properties in mouse models (Izumi et al, 2002).…”
Section: Mechanism Of Action Of Trastuzumab -Other Findingsmentioning
confidence: 99%
“…Loss of HER2/neu from the cell surface is incompatible with long-term growth of cell lines with high levels of HER2/neu expression such as SK-BR-3 (27), whereas cell lines that express low levels of HER2/neu seem to be less dependent on HER2/neu expression for their survival (27). In fact, an increased rate of HER2/neu internalization is considered an important intrinsic mechanism of trastuzumab action in therapy (28,29). Although we did not explore the mechanism through which the fusion proteins decreased tumor cell survival, it is plausible that fusion to C5a or C5a desArg interfered with recycling of the fusion protein-HER2/neu complex at the cell membrane.…”
Section: Discussionmentioning
confidence: 99%